The Effect of Bleaching Materials on Wool (Journal of the College of Basic Education, 2025)
Wool was and still is one of the most important raw materials obtained from nature used in the textile industry, as ancient man used it when he wore sheep skins to cover his body and protect it from climatic fluctuations (cold weather), and the animal species is the source of these hairs. Wool is taken from sheep, goats and camels, and the hairs grow on the animal’s body and their function is to protect its body from external influences. Due to the widespread use of wool fibers in the spinning and weaving industry and because of the conditions in which the animal lives in its environment, it is exposed to the adhesion of dust and dirt, which forces it to be cleaned before use and get rid of impurities and some stains. Since wool is a protein material, it can be damaged when treated with the abrasive materials available in local markets, as there are materials that work to destroy and dissolve it. Due to its importance and use in various industries, whether it is pure wool or mixed with other materials, whether natural such as cotton and linen or synthetic such as nylon, acrylic, viscose and other materials, We have to find the appropriate materials and the appropriate proportions to clean it, whether before or after weaving. The current research included the research problem, which was summarized in the following question: To what extent is wool affected by the bleaching materials used in cleaning and removing stains? Is there a chemical substance that shortens wool without damaging its material or not? The importance, objectives and limits of the research, specifically the terms mentioned in the research title. The second chapter included the theoretical framework and a historical overview of the wool material. The third chapter included the research methodology used and the experiments conducted on wool, then the results and conclusions, then the recommendations and suggestions, and finally a list of the sources on which the research relied.